An evolutionary method for finding the optimal path connecting two settlements - Yu. I. Dement'ev; R. V. Zimin (Научный вестник МГТУ ГА, 2016)
The paper describes an evolutionary method and an algorithm for finding the optimal path connecting two settlements.